ENGLISH TEACHER ABILITY IN SPEAKING AND WRITING THROUGH DESRIPTIVE TEXT AND THE RELATIONSHIP - Putra, Hendra - (IAIN Syekh Nurjati Cirebon, 2021)
Objective: This study discusses about English teacher ability in speaking and writing through descriptive text. Ideally English teacher is perfect in all of skills English. But in this study the researcher just focusses on two skill that is speaking and writing skill. The purpose of this study is to know the ability of English teacher ability in speaking and writing through dscriptive text then make the relationship between speaking and writing ability. Method: The approach used in this research is quantitative approach. The researches uses writing and speaking test as as instrument. The population is english teacher located in West Sumatera. Then the sample is 3 English teachers as participant in this research. The sample is purposive sampling it is intended to resaerch only. Result:it can be shown that english teacher ability in writing is 75 it means that the ability English teacher in writing is good. Then English teacherâ€™sÂ ability in speaking is 63. It means that the ability of english teacher in speaking is sufficient. Conclussion: related to result above it can be concluded that the ability of english teacher in writing is higher than speaking. It can be seen from the scored above. It also can be said that speaking is more difficult for english teacher than writing through descriptive text.